PENGARUH PENGETAHUAN TENTANG INISIASI MENYUSU DINI TERHADAP PROSES LAKTASI PADA IBU NIFAS DI KLINIK SUNGGAL KOTA MEDAN TAHUN 2017 - Chrismis Novalinda Ginting (Universitas Prima Indonesia, 2018)
Mother's skin will adjust its temperature to the baby's needs. Warmth during breastfeeding can reduce the risk of death due to hypothermia (cold). Mother and baby feel more calm, so that helps breathing and baby heartbeats more stable. So babies are more rarely fussy. This study aims to determine the effect of knowledge on early breastfeeding initiation of lactation process in postpartum mother at Sunggal Clinic Medan Medan 2017. This research is quasy experimental with pre-test, treatment, and post-test. The population in this study 10 people. Thenik sampling in the study is to use saturated sampling that is as much as 10 people. The results of research conducted on 10 respondents in Sunggal Clinic Medan Medan in 2017 the majority of respondents are well knowledge as many as 8 people (80%), and a knowledgeable minority of 1 person (10%) and less 1 person (10%). With the obtained p-Value of 0.007 so that there is a difference of knowledge about initiation of breastfeeding before and after. The conclusion in this research is that the respondent's knowledge about Initiation of Early Breastfeeding on lactation process at Sunggal Clinic is good knowledge, and it is suggested to the respondent to further improve the knowledge about IMD.